A Preliminary Study on the Nicknames of the FIFA National Football Teams. (2nd April 2020) - Feng, Wang; Shuyue, Zhang; Cheng, Chen
Abstract : This study examines 315 nicknames of all the 211 FIFA national football teams (NFTs) as of January 2020. A preliminary analysis of these nicknames shows that they have statistically significant differences, suggesting subtle intercultural variation worthy of further investigation. It is hoped that this initial foray into these nicknames will inspire in-depth academic research at the continental and intercontinental levels.